Corruption in the Nigeria Police Force: A Response to a Hostile State - Chris Ifeanyi Oke (Khazanah Sosial, 2022)
Over the years, Nigerians have been confronted with police brutality and highhandedness. It is becoming a common happenstance to witness extra-judicial killings, disappearance of suspects and detainees from custody, rebellions and revolts among the rank and file, and of course, the usual giving and taking of bribes in all the nooks and crannies of the country wherever a policeman is sighted either at the police stations, checkpoints or public offices. Very few researchers have taken due care to examine the root causes of police malfeasances. A closer look at the state and condition of service of an average Nigerian police officer will reveal that he is working and operating under theÂ  most inhumane and vicious circumstance. The implication of this is that he becomes frustrated, disillusioned, resigns to fate and takes his destiny in his own hands. In his daily conducts, he manifests acts of corruption, lawlessness, violent and aggressive behaviours to the State. Qualitative method of data collection was adopted in this study. Data for the study was generated from secondary sources such as textbooks, journals, newspapers, the internet, etc., while frustration-aggression theory was deployed as the theoretical framework for the study. This research revealed that corruption and other unethical attitudes exhibited by the Nigerian Police Force are a response to the hostile milieu in which they are subjected to. The paper, therefore, recommends that the welfare of the police officers must be prioritized.Â